2013
DOI: 10.2139/ssrn.2245404
|View full text |Cite
|
Sign up to set email alerts
|

Complexity, Specialization, and Growth

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…However, by considering six different geographical regions separately, it is observed that only for Europe and North America the parameter on the density variable is significantly negative. In line with the "O-Ring theory", the evidence presented by Ferrarini and Scaramozzino (2016) supports the idea that, especially for advanced countries, it can be the case that the productivity-gains from more specialization are smaller than the associated productivity-losses due to increased complexity in production. Unlike Ferrarini and Scaramozzino, we focus solely on advanced (OECD) countries, employ a different econometric technique, and analyze how the balance between complexity and specialization (induced by input proliferation) contributes to affect not only the rate of economic growth, but also the joint long-run relation between population growth, economic growth, and markups.…”
Section: Related Literaturesupporting
confidence: 62%
See 3 more Smart Citations
“…However, by considering six different geographical regions separately, it is observed that only for Europe and North America the parameter on the density variable is significantly negative. In line with the "O-Ring theory", the evidence presented by Ferrarini and Scaramozzino (2016) supports the idea that, especially for advanced countries, it can be the case that the productivity-gains from more specialization are smaller than the associated productivity-losses due to increased complexity in production. Unlike Ferrarini and Scaramozzino, we focus solely on advanced (OECD) countries, employ a different econometric technique, and analyze how the balance between complexity and specialization (induced by input proliferation) contributes to affect not only the rate of economic growth, but also the joint long-run relation between population growth, economic growth, and markups.…”
Section: Related Literaturesupporting
confidence: 62%
“…Our paper shows that when this happens we should observe not only a different level of the growth rate of per capita income but also, and perhaps more importantly, a change in the relation between economic growth, population growth, and markups across countries. 7 Our work is especially related to Bucci (2013Bucci ( , 2015, Bucci and Raurich (2017), Ferrarini and Scaramozzino (2016), and Maggioni et al (2016). Unlike Bucci (2013), it is not an objective of this article to emphasize the growth effects of the so-called returns to specialization (Benassy, 1998) and their role in shaping the link between population growth-economic growth and between markupseconomic growth.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A robust and stable relationship between a country's productive structure and economic growth is documented by several studies (i.e., [23][24][25][26][27]). Economic complexity is highly correlated with income and can explain differences in economic performance [28]. It also can predict future economic growth ( [20,[29][30][31]).…”
Section: Economic Complexity: Measures and Interconnectionsmentioning
confidence: 99%